PERAN AUDIT INTERNAL DALAM UPAYA PENCEGAHAN KECURANGAN PENGELOLAHAN KEUANGAN DESA BLURI - Andini Ardy Margareta; Intan Ayu; Atiqo Mita Fauziyah; Sevia Musfita Neysa; Nur Maulidah Apriliah Mahmudah Fauziah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Transparent and accountable village financial management is a crucial requirement to prevent fraud in the use of village funds. This study aims to analyze the role of internal audit in preventing fraud in village financial management. The research method employed is a qualitative approach with a case study method, using primary data from in-depth interviews and secondary data from regulatory documents and previous studies. The findings indicate that the implementation of routine supervision, activity documentation, community involvement in village meetings, and the active role of the regional inspectorate in internal auditing significantly contribute to improving transparency and accountability in Bluri Village. A structured financial reporting mechanism and regular training for village officials strengthen the internal control system, while community participation creates effective social control over the use of village funds. These findings highlight the importance of risk-based internal audits and community engagement in building clean and integrity-driven village financial governance.